The Characteristics of Oil Occurrence and Long-Distance Transportation due to Injected Fluid in Tight Oil Reservoirs - Liu Yang; Jun Yang; Jian Gao; Xuhui Zhang (Advances in Polymer Technology)
In tight oil reservoirs, the injected fluid needs to travel a long distance to expel oil from the micro/nano-size pores to natural fractures or man-made fractures. The flow characteristics of injected fluid are not known well due to the long distance displacement and complex pore structure. In this study, the tight reservoir samples are from typical tight oilfield of China and the oil distribution characteristics are studied based on mineral composition, physical properties and pore size distribution. The long core displacement experiment is conducted based on injection of water, N2, and CO2, which aims to study the individual flooding feasibility. The results show that the oil mainly distributes in the form of spots and accumulates in the micro/nano-pores. Both oil spots and clay minerals have associated characteristics. The microfractures are not the storage space for oil spots, but can connect the oil spots to improve the mobility of the crude oil. In addition, the oil can achieve long distance migration under the injection of water, N2, and CO2, which presents different pressure distribution characteristics. The reservoir pressure of water flooding decreases first and increases later with displacement time. The reservoir pressure of N2 flooding rises gradually over displacement time. The reservoir pressure of CO2 flooding increases first and decreases over displacement time. In contrast to water flooding, N2, and CO2 can increase the reservoir energy, which contributes to tight oil production. In comparison, CO2 has better performances than N2 in terms of oil displacement efficiency. The study contributes to understanding the oil distribution characteristics and provides the guidance for field trials using different flooding techniques.